2020 IEEE 40th International Conference on Distributed Computing Systems (ICDCS) 2020
DOI: 10.1109/icdcs47774.2020.00015
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain Based Auditable Access Control for Distributed Business Processes

Abstract: The use of blockchain technology has been proposed to provide auditable access control for individual resources. However, when all resources are owned by a single organization, such expensive solutions may not be needed. In this work we focus on distributed applications such as business processes and distributed workflows. These applications are often composed of multiple resources/services that are subject to the security and access control policies of different organizational domains. Here, blockchains can p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Since then, following works utilize similar mechanisms by employing smart contracts as a building block to provide tamper-proof for resource assignment processes. We observe that the work by Akhtar et al [5] can be integrated with Blockchain Studio [98] and Sturm et al [127]. By taking local access control policies into account during configuration (L2), the work by Lopez-Pintado et al [81] addresses dynamic role assignments at runtime (L3).…”
Section: J Resource-aware Bps On Bcmentioning
confidence: 98%
See 1 more Smart Citation
“…Since then, following works utilize similar mechanisms by employing smart contracts as a building block to provide tamper-proof for resource assignment processes. We observe that the work by Akhtar et al [5] can be integrated with Blockchain Studio [98] and Sturm et al [127]. By taking local access control policies into account during configuration (L2), the work by Lopez-Pintado et al [81] addresses dynamic role assignments at runtime (L3).…”
Section: J Resource-aware Bps On Bcmentioning
confidence: 98%
“…Using typical evaluation techniques will result in high overhead. To alleviate this, only one study is found by Akhtar et al [5] which try to optimize the collection of individual policies towards composite unified policies. The policy specification follows XACML standard, which will be translated into smart contracts for enforcement and audit purpose.…”
Section: J Resource-aware Bps On Bcmentioning
confidence: 99%
“…Instead, we can leverage the fact that for effective validation, it is not necessary to recheck all the accesses, but only a random fraction of them. We have proposed a gametheoretic mechanism for auditing that reduces the auditing cost while incentivizing honest behavior for the BPM in [2].…”
Section: Auditingmentioning
confidence: 99%
“…We note that an initial study of this problem was conducted in [2] where we also proposed a blockchain-based solution for auditable evaluation of access control policies of distributed BPs. However, [2] only considered static policies, whereas this work can be used for event-driven policies which are dynamic in nature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation